2019
DOI: 10.1158/0008-5472.can-18-3592
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methylation of Adenosine of FZD10 mRNA Contributes to PARP Inhibitor Resistance

Abstract: Despite the high initial response rates to PARP inhibitors (PARPi) in BRCA-mutated epithelial ovarian cancers (EOC), PARPi resistance remains a major challenge. Chemical modifications of RNAs have emerged as a new layer of epigenetic gene regulation. N 6 -methyladenosine (m 6 A) is the most abundant chemical modification of mRNA, yet the role of m 6 A modification in PARPi resistance has not previously been explored. Here, we show that m 6 A modification of FZD10 mRNA contributes to PARPi resistance by upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 25 publications
0
131
0
Order By: Relevance
“…FZD7(+) cells were shown to proliferate more robustly as spheres, to express higher levels of stemness associated TFs, Sox2 and Nanog, and be enriched in a stemness transcriptomic signature. Interestingly, a related receptor, FZD10, was recently reported as a marker of resistance to PARP inhibitors (42). Thus, it is likely that activation of the Wnt pathway through activation of one or more of the FZD receptors is linked to resistance to DNA-damaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…FZD7(+) cells were shown to proliferate more robustly as spheres, to express higher levels of stemness associated TFs, Sox2 and Nanog, and be enriched in a stemness transcriptomic signature. Interestingly, a related receptor, FZD10, was recently reported as a marker of resistance to PARP inhibitors (42). Thus, it is likely that activation of the Wnt pathway through activation of one or more of the FZD receptors is linked to resistance to DNA-damaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although this protective effect has been attributed to the downstream effectors of Wnt/b-catenin signaling such as survivin in one study, more generally the underlining mechanism still remains unclear (Watson et al, 2010;Gao et al, 2013;Nagano et al, 2013;Emons et al, 2017). Two recent studies found that elevated Wnt signaling enhanced the DNA damage repair and thereby conferred resistance to the PARP inhibitor olaparib in ovarian cancers (Fukumoto et al, 2019;Yamamoto et al, 2019). This mechanism could also protect cancer cells from DNA damage caused by other conventional chemo agents or radiation.…”
Section: Wnt Signaling Mediated Resistance In Cancer Therapymentioning
confidence: 99%
“…Wnt/b-catenin signaling mediated resistance to PARP inhibition in ovarian cancer due in part to upregulation of DNA damage repair. Inhibition of b-catenin signaling reverted resistance to olaparib in ovarian cancer xenografts (Fukumoto et al, 2019;Yamamoto et al, 2019). Vismodegib (Hedgehog signaling inhibitor)…”
Section: Resistance To Wnt Pathway Blockade In Normalmentioning
confidence: 99%
“…However, in epithelial ovarian cancers (EOC) with BRCA mutation, downregulation of FTO confers resistance to PARP inhibitors such as Olaparib, with m 6 A enrichment in 3 ′ -UTR regions of FZD10 and increased mRNA stability (61). FZD10 positively upregulates Wnt/β-catenin pathway and further promotes activity of homologous recombination.…”
Section: Wtapmentioning
confidence: 99%
“…Similar to FTO in BRCA-mutated EOC, expression of ALKBH5 is also inhibited, which activates Wnt/β-catenin pathway via stabilizing FZD10 mRNA and renders cell resistance to Olaparib (61).…”
Section: Alkbh5mentioning
confidence: 99%